Comparative Evaluation of Different Insecticides against Damage Caused by Sitophilus oryzae L. in Stored Wheat Seed - Mishra, Rajanish Chandra; Pandey, Rohit Kumar (International Journal of Bio-resource and Stress Management, 2023)
Today in the era of increasing population of country has intensified the enhanced need for higher food production. The intensification of food production has led to several problems in the post-harvest phase including the major concern of pest infestation during storage. Therefore, seven insecticides, viz., neem seed kernel powder (NSKP), neem cake, dry neem leaf powder (all @ 10 g kg-1), neem oil (10 ml kg-1), nimbecidine (5 and 10 ml kg-1) and deltamethrin 2.5 WP (40 mg kg-1) were evaluated as seed protectant against Sitophilus oryzae L. in stored wheat seed (HUW 234). In a sample size of two kg in gunny bags, adult were released @ 10 pairs bag-1 and bags were stored at room temperature. Data on infestation, weight loss and germination percentage were recorded at an interval of 3, 6 and 9 months after storage. The results revealed that deltamethrin was found most effective insecticides without harming germination for controlling of gain infestation and weight loss followed by neem India, at higher and lower doses, nimbecidine at higher and lower dose, neem oil, neem cake, dry neem leaf powder and NSKP treatments.